Зрілість бізнес-процесів як основа для оцінки економічної безпеки підприємства торгівлі - Коптєва (Фадєєва), Ганна Миколаївна (Видавничий дім "Інжек", 2020)
Цілісне розуміння стану економічної безпеки підприємства забезпечує реалізація процесного управління та оцінка безпеки на основі зрілості бізнес-процесів. Упровадження заходів щодо підвищення економічної безпеки підприємства на засадах зрілості бізнес-процесів дозволяє оптимізувати операційну та інвестиційну діяльність підприємства та забезпечує його захищеність від ризиків непослідовного впровадження заходів за сферами діяльності. Метою дослідження є обґрунтування зрілості бізнес-процесів підприємства торгівлі як критерію їх економічної безпеки та на цій основі розробка системи оцінки економічної безпеки бізнес-процесів підприємства. Підґрунтя для ув’язування концепцій процесного управління та управління безпекою становлять економічні інтереси підприємства, які мають бути захищені (з точки зору економічної безпеки) та реалізовані (з точки зору процесного управління). Виділено атрибути зрілості бізнес-процесів (захищеність бізнес-процесу з урахуванням реалізації інтересів стейкхолдерів, повнота реалізації бізнес-процесу) та критерії оцінки за ними (результативність, ефективність, якість, завершеність циклу управління), які враховано для формалізації системи оцінки рівня економічної безпеки підприємства на основі зрілості їх бізнес-процесів. Розроблена система показників оцінки бізнес-процесів підприємства торгівлі дозволяє ідентифікувати рівень зрілості бізнес-процесів та визначити на цій підставі рівень економічної безпеки підприємства. Перспективами подальших досліджень у даному напрямі є обґрунтування науково-методичного підходу до оцінки економічної безпеки підприємства торгівлі на основі зрілості його бізнес-процесів.

A holistic understanding of the state of economic security of enterprise is ensured by the implementation of process management and assessment of security based on the maturity of business processes. Introduction of measures to improve the economic security of the enterprise on the bases of maturity of business processes allows to optimize the operational and investment activities of the enterprise and ensures its safety against the risks of inconsistent implementation of measures in accordance with the spheres of activity. The purpose of the research is to substantiate the maturity of the business processes of trade enterprise as a criterion for their economic security and on this basis the development of a system for assessing the economic security of the business processes of the enterprise. The ground for linkage of conceptions of process management and security management are the economic interests of the enterprise, which have to be protected (in terms of economic security) and implemented (in terms of process management). The attributes of maturity of business processes (safety of business process taking into account the materialization of the stakeholders’ interests, completeness of business process implementation) and the criteria for evaluation on their basis (effectiveness, efficiency, quality, completion of the management cycle) are allocated, which are taken into account for the formalization of the system of assessment of the level of economic security of the enterprise on the basis of maturity of their business processes. The developed system of indicators for assessment of business processes of trade enterprise allows to identify the level of maturity of business processes and determine on this basis the level of economic security of the enterprise. Prospects for further research in this direction are the substantiation of a scientific-methodological approach to the assessment of economic security of trade enterprise on the basis of maturity of its business processes.
Maturity of business processes as a basis for assessing the economic security of trade enterprise
Keywords: конкурентоспроможність; економіка; управління; менеджмент; українські компанії; business process; maturity of business process; model of maturity of business process; economic security; safety of business process; assessment of the level of economic security